INTEGRASI NILAI BUDAYA DALAM KEPERAWATAN IBU DAN ANAK : SYSTEMATIC REVIEW PERSPEKTIF LEININGER - Nur, Rezeki; Hestiani K, Dewi; Najamuddin, Nur Isriani (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2026)
Background: The effectiveness of maternal and child nursing care is influenced not only by clinical interventions but also by the integration of patients’ cultural values into the care process. In multicultural contexts, cultural mismatches between healthcare providers and families may reduce service utilization, therapeutic communication quality, and adherence to care plans. A comprehensive theoretical framework is required to systematically analyze cultural integration in maternal and child nursing practice. Objective: This study aimed to synthesize empirical evidence on the integration of cultural values in maternal and child nursing care using the Transcultural Nursing perspective of Leininger and to map the findings into the components of the Sunrise Model. Method: This study employed a systematic review with a narrative synthesis approach following the PRISMA 2020 guidelines. Literature was identified through structured database searches using keywords related to transcultural nursing, cultural competence, maternal nursing, and child nursing. Empirical studies focusing on cultural integration in maternal and child nursing and available in full text were included. Data were extracted using a structured form and analyzed by mapping findings into the domains of the Sunrise Model and the three modes of action: cultural preservation, accommodation, and repatterning. Results: Eight empirical studies met the inclusion criteria. The synthesis revealed that cultural integration predominantly occurs within the domains of education, social-kinship structure, and healthcare systems. Cultural accommodation emerged as the most frequently applied mode of action, particularly in negotiating clinical standards with patients’ cultural values. Cultural preservation was relevant when religious and family practices did not compromise safety, while cultural repatterning was required in situations involving value conflicts or communication barriers. Organizational support and culturally competent education were identified as critical factors enabling culturally congruent care. Conclusion: The integration of cultural values in maternal and child nursing is a multidimensional process involving individual competence, family dynamics, and organizational structures. Leininger’s Sunrise Model provides a comprehensive analytical framework to guide culturally sensitive nursing practice in multicultural settings.